2015
DOI: 10.3389/fmed.2015.00010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Benfotiamine in Podocyte Damage Induced by Peritoneal Dialysis Fluid

Abstract: Background: In peritoneal dialysis (PD), residual renal function (RRF) fundamentally contributes to improved quality of life and patient survival. High glucose and advanced glycation end-products (AGE) contribute locally to peritoneal and systemically to renal damage. Integrity of podocyte structure and function is of special importance to preserve RRF. Benfotiamine could counteract the glucose and AGE-mediated toxicity by blocking hyperglycemia-associated podocyte damage via the pentose-phosphate pathway.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…We found similar effect of benfotiamine on morphological changes in dendritic cells which also undergo enlargement of the cell body and reorganization of the actin cytoskeleton after LPS stimulation, however benfotiamine reversed these changes, returning them to control levels [ 86 ]. Muller-Krebs et al, also found that benfotiamine restores reorganization of actin cytoskeleton of podocytes that were exposed to high glucose concentrations [ 88 ]. Cytoskeleton reorganization in activation of microglia has been attributed to activation of MAPK signaling cascade, specifically ERK1/2, p38 and JNKs were found to be partly responsible for morphological activation of microglia [ 89 ].…”
Section: Methodsmentioning
confidence: 99%
“…We found similar effect of benfotiamine on morphological changes in dendritic cells which also undergo enlargement of the cell body and reorganization of the actin cytoskeleton after LPS stimulation, however benfotiamine reversed these changes, returning them to control levels [ 86 ]. Muller-Krebs et al, also found that benfotiamine restores reorganization of actin cytoskeleton of podocytes that were exposed to high glucose concentrations [ 88 ]. Cytoskeleton reorganization in activation of microglia has been attributed to activation of MAPK signaling cascade, specifically ERK1/2, p38 and JNKs were found to be partly responsible for morphological activation of microglia [ 89 ].…”
Section: Methodsmentioning
confidence: 99%
“…Benfotiamine activates transketolase and has antioxidative effects in diabetes. This drug is proven to protect tissue from high-glucose–induced cell damage via alleviation of AGE accumulation [ 79 , 80 , 81 ]. Pyridoxamine inhibits AGE formation in vitro [ 82 ], and inhibits albuminuria in streptozotocin-induced diabetic rats [ 83 ].…”
Section: Intervention In Renal Glycative Stressmentioning
confidence: 99%
“…[2][3][4] Podocytes, a specialized epithelial cell in outer surfaces of glomerular capillaries, are implicated in the progression of DN. 5,6 High blood sugar often leads to podocyte apoptosis and increased urine protein. 7,8 Current treatments of DN has great limitations, and patients in terminal stage have impaired quality of life and high mortality rate.…”
Section: Introductionmentioning
confidence: 99%